Enriching Selves in Strength and Conditioning Society: A Multilevel Proposal to Enhance Strength and Conditioning Psychosocial Practice as Part of the Council on Accreditation of Strength and Conditioning Education. Issue 2 (April 2021) - Gearity, Brian T.; Szedlak, Christoph; Kuklick, Clayton R.; Mills, Joseph; Feit, Mary Kate; Callary, Bettina; Feit, Adam; Bergan, Maura
Abstract : ABSTRACT: This review article advances the longstanding need to address psychosocial issues within strength and conditioning (S&C) that have renewed significance with the National Strength and Conditioning Association's entry into accreditation. First, a brief history is presented on the omission of psychosocial issues within S&C and the education of S&C practitioners. Second, the article provides an overview of learning theory and instructional strategies on how to develop essential psychosocial competencies of S&C practitioners. Third, multilevel recommendations are offered to address established calls to improve the education of S&C practitioners, ongoing accreditation efforts, and continued structural changes throughout the growing, global profession of S&C coaching.